R&D products od universities in Malaysia, 2012 - Yahaya Abd. Aziz (Jabatan Pengajian Tinggi, Kementerian Pendidikan Malaysia, 2013)
The "R&D Products of Universities in Malaysia 2012" is a book documenting and describing innovative products developed by researchers at Public Higher Education Institutions (Public HEI's) and Private Higher Education Institutions (Private HEI's). This book is aims to publicize information on the products and discoveries from local universities to public, especially to local developer and industrialists. It is also to support universities' research projects and inventions to a level where they can be commercialized.